Pretreatment Of Oil Palm Frond By Phanerochaete Crysosporium Ck01 And Enzymatic Hydrolysis For Ethanol Production By Saccharomyces Cerevisiae Hc10 - Halim, Farah Amani Abdul (2018)
Oil palm frond (OPF) is one of the most abundant waste generated from an oil palm plantation. OPF can be utilized as a feedstock for bioethanol and can simultaneously address its disposal issue in the plantation. In this project, OPF was divided into two types of feedstock; biomass and juice by mechanical pressing. Firstly, the dried biomass was biologically treated using white-rot fungi; Phanerochaete chrysosporium CK01 for biodelignification. Two parameters were tested; effect of inoculum size and fermentation duration. The best parameters were inoculum size of 1.0x106 spore/mL and 3 weeks of fermentation duration which gave 27.87% of delignification. In the second stage, the treated biomass was subjected to enzymatic hydrolysis by either individual or in combination to produce a sugar hydrolysate. Two parameters tested were enzyme loading (in individual enzymatic hydrolysis) or enzyme ratio (in combined enzymatic hydrolysis; Cellulase A “Amano” 3 and Hemicellulase “Amano” 90) and hydrolysis time. The result shows that the combined (cellulase and hemicellulase) enzymatic hydrolysis produces higher amount of simple sugar (5.15g/L) using a combination of enzyme ratio of 1:4 (cellulase:hemicellulase) with a hydrolysis time of 120 minutes compared to individual enzymatic hydrolysis (3.26g/L). Prior to beginning of the third stage, the amount of simple sugar in the hydrolysate (OPFH) and juice (OPFJ) were compared using high performance liquid chromatography (HPLC) analysis.